High INtensity Interval Training In pATiEnts with intermittent claudication (INITIATE): protocol for a multicentre, proof-of-concept, prospective interventional study - Gordon McGregor; Chao Huang; Maureen Twiddy; Judith Long; Amy Harwood; Lee Ingle; Saïd Ibeggazene; Sean Pymer; Adam R Nicholls; Sean Carroll; Marjorie Rooms; I C Chetter (BMJ Open)
Introduction The first-line recommended treatment for patients with intermittent claudication (IC) is a supervised exercise programme (SEP), which includes a minimum of 2-hours of exercise per week over a 12-week period. However, provision, uptake and adherence rates for these SEP programmes are poor, with time constraints cited as a common participant barrier. High-intensity interval training (HIIT) is more time-efficient and therefore has the potential to overcome this barrier. However, evidence is lacking for the role of HIIT in those with IC. This proof-of-concept study aims to consider the safety, feasibility, tolerability and acceptability of a HIIT programme for patients with IC.Methods and analysis This multicentre, single-group, prospective, interventional feasibility study will recruit 40 patients with IC, who will complete 6 weeks of HIIT, 3 times a week. HIIT will involve a supervised programme of 10×1 min high-intensity cycling intervals at 85%–90% peak power output (PPO), interspaced with 10×1 min low intensity intervals at 20%–25% PPO. PPO will be determined from a baseline cardiopulmonary exercise test (CPET) and it is intended that patients will achieve ≥85% of maximum heart rate from CPET, by the end of the second HIIT interval. Primary outcome measures are safety (occurrence of adverse events directly related to the study), programme feasibility (including participant eligibility, recruitment and completion rates) and HIIT tolerability (ability to achieve and maintain the required intensity). Secondary outcomes include patient acceptability, walking distance, CPET cardiorespiratory fitness measures and quality of life outcomes.Ethics and dissemination Ethical approval was obtained via a local National Health Service research ethics committee (Bradford Leeds – 18/YH/0112) and recruitment began in August 2019 and will be completed in October 2020. Results will be published in peer-reviewed journals and presented at international conferences and are expected to inform a future pilot randomised controlled trial of HIIT versus usual-care SEPs.Trial registration number NCT04042311; Pre-results.